2016
DOI: 10.1371/journal.pone.0151938
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Stem Cell Therapy for Diabetes Mellitus: A Meta-Analysis

Abstract: BackgroundStem cell therapy is a promising therapeutic modality for advanced diabetes mellitus (DM). This study presents a meta-analysis of relevant clinical trials to determine the efficacy of stem cell therapy in DM. We aim to critically evaluate and synthesize clinical evidence on the safety and efficiency of different types of stem cell therapy for both T1DM and T2DM.Methods and FindingsWe pooled participant-level data from twenty-two eligible clinical trials that satisfied our inclusion criteria, with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 59 publications
2
86
0
3
Order By: Relevance
“…For type 1 diabetes mellitus (T1D), both hematopoietic stem cell (HSC) transplantation and mesenchymal stem cell (MSC) transplantation have been evaluated (Cantu-Rodriguez et al, 2016;Cheng et al, 2016;El-Badawy and El-Badri, 2016;Snarski et al, 2016;Xiang et al, 2016;Xv et al, 2016). These studies have shown that HSC and MSC transplantations improve blood glucose levels from moderate to high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For type 1 diabetes mellitus (T1D), both hematopoietic stem cell (HSC) transplantation and mesenchymal stem cell (MSC) transplantation have been evaluated (Cantu-Rodriguez et al, 2016;Cheng et al, 2016;El-Badawy and El-Badri, 2016;Snarski et al, 2016;Xiang et al, 2016;Xv et al, 2016). These studies have shown that HSC and MSC transplantations improve blood glucose levels from moderate to high.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that HSC and MSC transplantations improve blood glucose levels from moderate to high. The meta-analysis study carried out by El-Badawy and El-Badri (2016) showed that the best therapeutic outcome could be achieved with CD34+ HSC transplantation, while the poorest outcome was observed with umbilical cord blood transplantation (El-Badawy and El-Badri, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis study compared several clinical trials utilizing various stem cells for the treatment of diabetes mellitus. 24 Although this meta-analysis showed that therapy with CD34 + hematopoietic stem cells showed a superior outcomes, this study has several serious limitations, such as including only a small number of trials, which in turn include only a low number of patients, and the follow-up period was not sufficiently long in order to build any significant conclusion. Finally, although the results of the currently available clinical trials involving MSCs in treating diabetes are encouraging, it is necessary to have larger, randomized, and double-blinded studies, with a longer duration of follow-up, in order to validate the findings obtained.…”
Section: Discussionmentioning
confidence: 91%
“…DM affects millions of people worldwide and is associated with serious complications that affect all body organs [78][79][80]. The available therapeutic modalities for DM include: diet and lifestyle modifications, oral hypoglycemic agents, insulin injections and islet cell transplantation [79,81,82].…”
Section: Journal Of Stem Cell Biology and Transplantation Issn 2575-7725mentioning
confidence: 99%